India in Space: Between Utility and Geopolitics - Aliberti, Marco (Studies in Space Policy,, 2018)
This book presents the renewing strategic vision and progressive diversification of the Indian space programme at the nexus socio-economic development, commerce and geopolitics. It disentangles India ́s evolving rationales for engaging in space from a wide range of perspectives and provides novel and in-depth assessment of the domestic, regional and international factors influencing the pace and directions of the country's space programme. The study hence includes an extensive analysis of India's path forward, including a reflection on the long-term evolution of its civil, military and commercial space efforts, as well as considerations on the toolbox India has at its disposal, on the prospected adaptation of the space ecosystem, and on the implications these evolutions may generate both domestically and internationally. A central part of this final analysis is more specifically devoted to elaborating on the prospects and opportunities for European stakeholders, with the goal of identifying possible domains of closer and mutually beneficial Europe-India space cooperation and sorting out possible elements for a comprehensive European long-term strategy towards India.